2019
DOI: 10.1111/aje.12696
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different anthropogenic disturbances on litterfall of a dominant pioneer rain forest tree in Gabon

Abstract: Tropical rain forests worldwide are affected by anthropogenic disturbances, and secondary forests that develop afterwards are often dominated by pioneer tree species, but the consequences of different anthropogenic disturbances on nutrient cycling are poorly understood. Because most nutrient cycling in tropical rain forests occurs through litterfall and in the soil organic layer, we measured litterfall of a widespread and dominant pioneer tree, okoume (Aucoumea klaineana, Burseraceae) in Gabon, in one forest p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 60 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…Litterfall is closely related to the seasonal dynamics of old leaves (i.e., LAI old ; Yang et al, 2021). Previous analyses indicated that, in general, a sharp decrease in LAI old corresponded to a peak in litterfall (Pastorello et al, 2020;Midoko Iponga et al, 2019;Ndakara, 2011;Barlow et al, 2007;Dantas and Phillipson, 1989). Based on this causal relationship between litterfall and LAI old , we compared the time of seasonal litterfall peak with the time of abrupt drops in LAI old to indirectly evaluate the simulated LAI old seasonality.…”
Section: Evaluating the Lai Old Seasonality Using Ground-based Litter...mentioning
confidence: 99%
“…Litterfall is closely related to the seasonal dynamics of old leaves (i.e., LAI old ; Yang et al, 2021). Previous analyses indicated that, in general, a sharp decrease in LAI old corresponded to a peak in litterfall (Pastorello et al, 2020;Midoko Iponga et al, 2019;Ndakara, 2011;Barlow et al, 2007;Dantas and Phillipson, 1989). Based on this causal relationship between litterfall and LAI old , we compared the time of seasonal litterfall peak with the time of abrupt drops in LAI old to indirectly evaluate the simulated LAI old seasonality.…”
Section: Evaluating the Lai Old Seasonality Using Ground-based Litter...mentioning
confidence: 99%